The Influence of Job Characteristics, Perceived Organizational Support, and Person-Environment Fit on Job Satisfaction, Which Impacts Job Search Behavior - Vincentia Olivia Kenya Laksitaningtyas; Kusdi Raharjo; Gunawan Eko Nurtjahjono (PT. Global Research Collaboration, 2026)
This study is motivated by the increasing number of Generation Z employees who tend to leave their organizations when their workplace expectations are not fulfilled. This phenomenon occurs globally and in Indonesia, where Generation Z now represents more than a quarter of the population and plays an increasingly important role in the labor market. However, many of them report dissatisfaction due to unmet expectations, which leads to higher job-search behavior. This study examines how job satisfaction mediates the effects of job characteristics, perceived organizational support, and person–environment fit on job search behavior among Generation Z employees in startup companies. This study used an explanatory quantitative approach. Primary data were collected through questionnaires distributed to all Generation Z employees in five startup companies: PT Digdaya Olah Teknologi Indonesia, Skybox Digital Imagery, Codespace Indonesia, Letsplay Indonesia, and CMLABS Indonesia Digital, with a total sample size of 189 respondents. Data were analyzed using SmartPLS (PLS-SEM). The findings indicate that Job characteristics, perceived organizational support, and person–environment fit each had a positive and significant effect on job satisfaction. Job satisfaction significantly and negatively affected job-search behavior. Additionally, job satisfaction mediated the relationship between the three independent variables and job search behavior. The model explains R² = 0.594 of job search behavior variance, and all seven hypotheses are supported. Improving job characteristics, strengthening organizational support, and enhancing person–environment fit significantly increase job satisfaction, which, in turn, reduces job search behavior among Generation Z employees in startup companies.